Pengaruh Peer Education terhadap Sikap Remaja tentang Pernikahan di Kabupaten Mimika - Neny San Agustina Siregar; Dedy Arisjulyanto; Tri Noviyanti Mansur; Yumi Abimulyani (Pusat riset dan Inovasi Nasional, 2025)
Early marriage is a social issue that negatively impacts adolescents' health, education, and overall well-being. Mimika Regency is one of the regions with a relatively high rate of early marriages. This study aimed to analyze the effect of the peer education method on adolescents’ attitudes toward marriage in Mimika Regency. This research employed a quasi-experimental design with a pre-test and post-test approach. The study population consisted of adolescents aged 15–18 years residing in Mimika Regency, with a total sample of 65 respondents selected using purposive sampling. The research instrument was an attitude questionnaire that had been tested for validity and reliability, with a Cronbach’s alpha score of 0.904, indicating that the instrument was reliable. Data were collected through a pre-test before the intervention and a post-test after the implementation of peer education. The results showed that the average score of adolescents' attitudes toward early marriage increased from 21.32 before the intervention to 30.98 after the intervention. Statistical analysis revealed a p-value of 0.000 (< α = 0.05), indicating a significant effect of peer education on adolescents’ attitudes toward marriage.Peer education significantly influences changes in adolescents’ attitudes in preventing early marriage in Mimika Regency.